Allelopathic Potential of Hemp: Implications for Integrated Weed Management - Shikanai, Avery; Gage, Karla L. (Frontiers in Agronomy, 2022)
Evolved resistance to herbicides necessitates alternative weed control strategies. Allelopathic crops show promise as an alternative to exogenous herbicides and could be used to reduce establishment, growth, and reproduction of weeds. Individual cannabinoids and terpenes found in hemp (Cannabis sativa L.) show allelopathic potential, but allelopathic effects of plant residue have not been characterized. A laboratory assay found that crude, acetone-soluble hemp extracts diluted to 2.5 mg mL-1 reduced the germination of a bioindicator species. However, tested concentrations below 2.5 mg mL-1 were not more effective than the no-extract control treatment at reducing germination. A greenhouse study found that soil-incorporated hemp residue was not more effective than a maize (Zea mays L.) residue treatment comparison in reducing plant growth. However, a simulated chaff line experiment in the greenhouse showed that the equivalent of 378 g m-2 hemp residue on the soil surface can effectively reduce and delay the germination of waterhemp [Amaranthus tuberculatus (Moq.) Sauer] in comparison to bare-soil, or a maize residue treatment comparison. Together, these results show that incorporated hemp residue will likely not be an effective weed control practice. However, chaff lining hemp residue may be an effective practice for the control of certain weeds and warrants further research in a field setting.